Unveiling the nexus between empathy and leadership in the production sector - Miklosh Bojan; Janeska iliev, Aleksandra; Drakulevski, LJubomir (The Faculty of Economics - Prilep , University “St. Kliment Ohridski” – Bitola., 2024)
Work in the production and manufacturing sector is characterized by following strict procedures, meeting norms and targets, upholding standards, and producing results and products that are entering the market. Considering these characteristics, leading people and teams in this context may pose a challenge, especially if the leaders are not aware of their emotional intelligence or, are lacking crucial social skills, thus reflecting and embedding various norms in the organizational culture. Experts have been researching organizational cultures, as well as the relationship between leadership styles and emotional intelligence, building knowledge on findings, usually following Dr. Goleman’s scholarly work. Thus, the focus of the research in this manuscript is directed toward exploiting empirical data to explore specific leadership styles in relation to emotional intelligence within a specific organizational context- the manufacturing sector. Drawing insights from 125 respondents, this research utilizes a questionnaire designed with validated research instruments. Findings reveal a strong overall correlation value between leadership styles and emotional intelligence competencies, especially emphasizing the link to transformational styles. The results reveal an interesting combination of leadership styles and emotional intelligence competencies. Namely, the commanding and visionary leadership styles emerge as the most prevalent styles, and empathy and conflict management as the only emotional intelligence competencies with an above-average value. The least mastered EI competence in the production sector is the emotional self-control, opening a field of opportunities for development and improvement. Overall, this research reaffirms the link between leadership and emotional intelligence.
Keywords: production; leadership, emotional intelligence; style; relationship.